Angle-Specific Isokinetic Metrics Highlight Strength Training Needs of Elite Youth Soccer Players. Issue 11 (November 2020) - Eustace, Steven J.; Page, Richard M.; Greig, Matt
Abstract : Abstract: Eustace, SJ, Page, RM, and Greig, M. angle specific isokinetic metrics highlight strength training needs of elite youth soccer players. J Strength Cond Res 34(11): 3258–3265, 2020—The purpose of this study was to assess traditional and angle-specific isokinetic strength of eccentric knee flexors (eccKFs) and concentric knee extensors (conKEs) between senior professional and youth soccer players. Thirty-four male soccer players (17 senior and 17 youth) were recruited for bilateral assessments at 180, 270, and 60°·s −1 . Peak torque (PT), dynamic control ratio (DCR), angle of peak torque (APT), functional range (FR), angle-specific torque (AST), and angle-specific DCR (DCRAST ) were compared. The eccentric knee flexor (eccKF) and conKE PT ( p = 0.782) and DCR ( p = 0.508) were not different between groups across all angular velocities. Significant differences were identified for eccKF APT ( p = 0.018) and FR ( p = 0.006), DCRAST at 270°·s −1 ( p = 0.031), and in AST data recorded across angular velocities for eccKF and conKE ( p = 0.003). Traditional strength measures were not sensitive to playing age, with implications for misinterpretation in training prescription. By contrast, AST data did differentiate between ages. Strength deficits that highlight the muscle contraction type, angular velocity, and joint angle can be manipulated within an individualized training intervention. Given the relevance to injury etiology, this study highlights potential implications for improved assessment strategies to inform training prescription for performance and injury prevention. Given the high number of injuries in adolescent soccer players, and in line with previous recommendations, practitioners should consider using more informed and specific strength and conditioning practices at younger ages.